The Impact of Adhering to The Professional Framework Standards, According to The Guidance Manual, on Enhancing the Auditor's Reliance on Internal Audit Activities in Support of The Quality of Financial Reports (Al-Mansour Journal, 2026)
This research aims to demonstrate the impact of adhering to the professional framework standards for internal auditing, based on the guidelines issued by the Federal Board of Supreme Audit, on enhancing the external auditor's reliance on internal audit activities and outputs, and the resulting impact on the quality of financial reports in Iraq. The research's significance stems from the challenges faced by auditors due to the expanding scale and complexity of economic units' operations, and the trend towards adopting international auditing standards, particularly INTOSAI Standard 2610 and International Standard on Auditing (ISA 610) concerning the use of internal auditor activities. The research employed a descriptive-analytical methodology and was conducted through a questionnaire distributed to a sample of internal and external auditors in economic units belonging to the public and mixed sectors across several key sectors, including banking, services, industry, agriculture, hotels and tourism, education, insurance, and healthcare. A total of 209 questionnaires were deemed valid for statistical analysis.  The results showed that internal audit practices focus on acquiring skills and knowledge related to detecting errors and fraud, while exhibiting a relative weakness in organizational independence and adherence to quality requirements. This limits the degree to which external auditors rely on internal audit work. The research recommends strengthening adherence to the standards of the Professional Framework for Internal Auditing and activating the provisions of the guidance manual to support integration between internal and external auditing and contribute to improving the quality and credibility of financial reports.
Keywords: Professional Framework standards; guidance manual; internal audit activities; financial reporting quality; Attribute Standards; Performance Standards